Characterization of Precipitation in Al-Li Alloy AA2195 by means of Atom Probe Tomography and Transmission Electron Microscopy - Muna Khushaim; Torben Boll; Judith Seibert; Ferdinand Haider; Talaat Al-Kassab (Advances in Condensed Matter Physics)
The microstructure of the commercial alloy AA2195 was investigated on the nanoscale after conducting T8 tempering. This particular thermomechanical treatment of the specimen resulted in the formation of platelet-shaped T1Al2CuLi/θ′Al2Cu precipitates within the Al matrix. The electrochemically prepared samples were analyzed by scanning transmission electron microscopy and atom probe tomography for chemical mapping. The θ′ platelets, which are less than 2 nm thick, have the stoichiometric composition consistent with the expected Al2Cu equilibrium composition. Additionally, the Li distribution inside the θ′ platelets was found to equal the same value as in the matrix. The equally thin T1 platelet deviates from the formula (Al2CuLi) in its stoichiometry and shows Mg enrichment inside the platelet without any indication of a higher segregation level at the precipitate/matrix interface. The deviation from the (Al2CuLi) stoichiometry cannot be simply interpreted as a consequence of artifacts when measuring the Cu and Li concentrations inside the T1 platelet. The results show rather a strong hint for a true lower Li and Cu contents, hence supporting reasonably the hypothesis that the real chemical composition for the thin T1 platelet in the T8 tempering condition differs from the equilibrium composition of the thermodynamic stable bulk phase.